Molecular identification of Haemaphysalis sulcata (Acari: Ixodidae) larval stages collected using the Berlese funnel in Northern Iran - Milad Davari; Masoud Hakimitabar; Asadollah Hosseini Chegeni (Persian Journal of Acarology)
Molecular detection techniques based on conventional PCR and sequencing of the partial genome of living organisms are considered an important tool for identification. BLASTn and comparison of evolutionary relationships between taxa are the next analysis steps on sequences. The construction of a phylogenetic tree is done using genetic distance difference; nucleotide substitution models and comparison with the outgroup. In the present study, two samples of tick larvae were collected in Mirafzal forest area (36°07'39.0"N 53°35'45.0"E) located in Mazandaran province, northern Iran using the Berlese funnel. Tick samples were initially identified using a generic identification key (Bregetova et al. 1955) and in order to determine specific identification of species, PCR of partial internal transcribed spacer 2 (ITS2) gene and Sanger sequencing were performed.  Morphological results showed that tick samples belonged to Haemaphysalis genus because they had a relatively short capitulum, no eyes with festoons. DNA extraction, PCR amplification and sequencing of a partial fragment (ca. 1400-bp) ITS2 gene of tick sample were done, successfully. The results of BLASTn showed that the larvae belonged to the species Haemaphysalis sulcata. A nucleotide DNA sequence of ITS2 was submitted to GenBank under the accession number MW929218. The molecular technique of this study is recommended to identify immature and dead tick samples that cannot be reared until the adult stage. The present study was the first report on the identification of H. sulcata larvae isolated from the Berlese funnel. The result of this study will help to better understand the biology of this tick and the presence of immature larval stages with questing behaviour in the soil environment.